Inanspruchnahme und Patientenprofil einer ambulanten Abteilung für Kinderzahnheilkunde in Deutschland - Westerwalbesloh, Claudia Beate; Justus Liebig University Giessen (My University, 2012)
In der vorliegenden Studie wurden die Inanspruchnahme und das Patientenprofil der ambulanten Abteilung für Kinderzahnheilkunde am Medizinischen Zentrum für Zahn-, Mund- und Kieferheilkunde der Justus- Liebig- Universität in Gießen untersucht und dabei auch der Gebisserkrankungs- und Gebisssanierungszustand der Patienten im Kindesalter analysiert.

This study examines the utilization and patient profile of the Poliklinik für Kinderzahnheilkunde (clinic of pediatric dentistry) outpatient ward at the medical centre of dental, oral and maxillofacial surgery of the Justus- Liebig- University in Giessen. In addition, the dental diseases and dental restoration of child patients were also examined.
Utilisation and patient profile of a outpatient clinic for pediatric dentistry in Germany
Keywords: Kinderzahnheilkunde; Inanspruchnahme; Patientenprofil; Epidemiologie; Gebisserkrankungsbefund; utilisation; patient profile; pediatric dentistry; ddc:610